Digital Marketing Strategies To Increase Sales (Case Study: Warung Wikko In Bangka Belitung) - Milano, Alycia Cindy; Kusumaningrum, Ni Ketut Veri; Agustini, I Gusti Ayu Ari (Politeknik Internasional Bali, 2025)
This study aims to analyse the digital marketing strategies implemented by Warung Wikko, a local culinary business in Pangkal Pinang, Bangka, in an effort to increase sales and maintain its existence amid increasingly competitive business competition. This study was motivated by a decline in sales turnover and limited use of digital media in promotional activities. This study uses a descriptive qualitative approach with data collection techniques in the form of interviews, observations, documentation, and distribution of questionnaires to active consumers of Warung Wikko. The theory used in this study is the AIDA (Attention, Interest, Desire, Action) model to analyse the effectiveness of digital strategies in influencing consumer purchasing decisions. The results show that Warung Wikko's digital marketing strategy has succeeded in attracting consumer attention and interest through social media, particularly Instagram and WhatsApp. However, the lack of content variety, consistency in posting, and calls to action has resulted in suboptimal desire and purchasing behaviour. This study recommends strengthening promotional content, optimising the use of digital features, and collaborating to increase market reach. A well-planned and sustainable digital strategy is expected to significantly boost Warung Wikko's sales.